Hepatoprotectivity of Panduratin A against liver damage: In vivo demonstration with a rat model of cirrhosis induced by thioacetamide - Salama, Suzy Munir; Ibrahim, Ibrahim Abdel Aziz; Shahzad, Naiyer; Al-Ghamdi, Saeed; Ayoub, Nahla; AlRashdi, Ahmed Salim; Abdulla, Mahmood Ameen; Salehen, Nur'ain; Bilgen, Mehmet (Wiley, 2018)
This experiment evaluated Panduratin A (PA), a chalcone isolated from Boesenbergia rotunda rhizomes, for its hepatoprotectivity. Rats were subjected to liver damage induced by intra-peritoneal injection of thioacetamide (TAA). PA was tested first for its acute toxicity and then administered by oral gavage at doses 5, 10, and 50 mg/kg to rats. At the end of the 8th week, livers from all rats were excised and evaluated ex vivo. Measurements included alkaline phosphatase (AP), alanine transaminase (ALT), aspartate transaminase (AST) and gamma-glutamyl transferase (GGT), serum platelet-derived growth factor (PDGF) and transforming growth factor (TGF-β1), and hepatic metalloproteinase enzyme (MMP-2) and its inhibitor extracellular matrix protein (TIMP-1). Oxidative stress was measured by liver malondialdehyde (MDA) and nitrotyrosine levels, urinary 8-hydroxy 2- deoxyguanosine (8-OH-dG), and hepatic antioxidant enzyme activities. The immunohistochemistry of TGF-β1 was additionally performed. PA revealed safe dose of 250 mg/kg on experimental rats and positive effect on the liver. The results suggested reduced hepatic stellate cells (HSCs) activity as verified from the attenuation of serum PDGF and TGF-β1, hepatic MMP-2 and TIMP-1, and oxidative stress. The extensive data altogether conclude that PA treatment could protect the liver from the progression of cirrhosis through a possible mechanism inhibiting HSCs activity.